Philippine GDP growth after the Asian financial crisis: Resilient economy or weak statistical system? - Felipe M. Medalla; Karl Robert L. Jandoc (University of the Philippines, School of Economics (UPSE), 2008)
Official statistics from the National Income Accounts (NIA) in the Philippines depicts an economy that has grown faster after the Asian Financial Crisis (AFC). Although the higher growth of output after the AFC was accompanied by higher real growth rates of personal consumption and the service sector, NIA statistics also identifies import growth compression as the dominant factor in the expenditure side of the NIA that accounts for the rise in the growth rate of the economy after the AFC. In this respect, the Philippine experience is quite different from much of Asia where the growth rates of domestic absorption (C+I+G), exports and imports rose or fell in tandem with the growth of GDP. This paper takes the view that the uniqueness of the Philippines maybe more a reflection of the weakness of its national income accounting system than the resiliency of its economy. In the first place, many trends within the NIA itself and data from FIES raise doubts regarding the supposed rise in the growth rate of personal consumption expenditures. There is also reason to believe that Agriculture may not be as robust, and that the growth of value added in palay and agriculture may have been overestimated. Data from the Monthly Integrated Survey of Selected Industries (MISSI) and Labor Force Surveys contradict the NIA's estimate of manufacturing growth. In the Services Sector, where growth is inherently hard to measure and imputations of value added are made, Personal Services and Wholesale and Retail Trade account for two thirds of the increase in the sector's contribution to the increase in GDP growth after the AFC. Given the weaknesses of the NIA and the fact that the trends in many other economic indicators outside the NIA seem to contradict it, it is very likely that GDP growth after the AFC (and after 2000 in particular) has been over-stated.
Keywords: 330; Sozialprodukt; Volkswirtschaftliche Gesamtrechnung; Philippinen